Augmenting effect of inclusive and ambidextrous leadership on public university academic staffs’ innovative performance: the mediating role of innovative work behavior - Ab Wahab, Faridah; Subramaniam, Anusuiya; Ho, Jo Ann; Bali Mahomed, Anuar Shah (SAGE Publications, 2024)
This study aims to address a gap in research by examining the relationship between leadership styles, innovative work behavior, and innovative performance among academic staff at public universities. Specifically, the study seeks to identify the extent to which inclusive and ambidextrous leadership styles can facilitate innovative performance, examine whether innovative work behavior enhances innovative performance, and discover whether innovative work behavior mediates the relationship between inclusive and ambidextrous leadership styles and innovative performance among academic staff at public universities. A critical survey was conducted using a questionnaire among academic staff at two public universities located on the east coast of Peninsular Malaysia, generating 300 responses. The study used SPSS 27.0 and SEM with AMOS 24.0 to analyze the results. The findings of this study show that inclusive and ambidextrous leadership are positively associated with innovative work behavior. The study also found that innovative work behavior facilitates innovative performance. The study highlights the mediating effect of innovative work behavior on the relationship between leadership styles and academic staff’s innovative performance, offering important insights into how public universities can improve their academic staff’s innovative performance through effective leadership and work behavior strategies.